2013
DOI: 10.12932/ap0289.31.3.2013
|View full text |Cite
|
Sign up to set email alerts
|

Recent 5-year trends of asthma severity and allergen sensitization among children in southern Thailand

Abstract: During the years between 2004 and 2009, asthma severity increased with increasing sensitization to HD, HDM and cockroach. Awareness of these changes and further studies are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 20 publications
(27 reference statements)
2
11
0
Order By: Relevance
“…Almost half of all families reported exposure to cockroach and/or mouse, posing a high allergen burden on these children and consistent with the increased prevalence of American cockroach sensitization among Thai children with asthma. 32 Positive cockroach sensitization was associated with almost a seven fold risk of high SABA use suggesting that the combination of sensitization and exposure to cockroaches may be a key contributor to asthma morbidity in inner-city children per prior reports. 33 Because only one-third of children had received prior allergy testing, most caregivers may be unaware of their child’s sensitization to cockroach and the increased risk for symptoms with exposure.…”
Section: Discussionmentioning
confidence: 83%
“…Almost half of all families reported exposure to cockroach and/or mouse, posing a high allergen burden on these children and consistent with the increased prevalence of American cockroach sensitization among Thai children with asthma. 32 Positive cockroach sensitization was associated with almost a seven fold risk of high SABA use suggesting that the combination of sensitization and exposure to cockroaches may be a key contributor to asthma morbidity in inner-city children per prior reports. 33 Because only one-third of children had received prior allergy testing, most caregivers may be unaware of their child’s sensitization to cockroach and the increased risk for symptoms with exposure.…”
Section: Discussionmentioning
confidence: 83%
“…This was consistent with previous studies in Thai children which had found that 61.6% of patients in 2004 and 64.6% of patients in 2009 with asthma had positive SPT results. 17 Moreover, 63.2% of asthmatic children had positive SPTs 18 and 89% of atopic asthmatic children were poly-sensitized. 16 Mild persistent severity was found in 74.2% and 70.4% of atopic and non-atopic asthma, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…House dust mite was also the most common allergen in poly-sensitization patients (90.5%), followed by American cockroach (61.5%), German cockroach (52.9%), The median age at onset for non-atopic asthma (negative SPT) was significantly younger than that of atopic asthma (positive SPT) [1.5 (0.1-13.0) vs. 2.0 (0.2-14.0) years; p<0.01]. The median age at onset for non-AR (negative SPT) was also significantly younger than that of AR (positive SPT) 17 A study in Sweden found that sensitization by SPT to cat, dog, birch, and timothy increased significantly from 1994 to 2009. 19 These changing allergen sensitizations may be attributable to global warming, which may affect aeroallergen distribution differently from area to area.…”
Section: Aeroallergen Sensitizationmentioning
confidence: 91%
“…[72, 73]. In a study carried out in Thailand, the possible changes in disease severity and allergen sensitization of children with asthma in an interim period of 5 years was evaluated [74]. During the years 2004-2009, asthma severity increased with increasing sensitization to mite and mite plus cockroach.…”
Section: Cockroach Allergens Sensitization and Severe Asthmamentioning
confidence: 99%